Implementation of the Rehabilitation Program for Unliable Housing in the Sub-District of Medan Tuntungan - Pratomo, Nanda Gusti; Manurung, Rudi Kristian P. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine and describe how the implementation of the rehabilitation program for uninhabitable houses in Medan Tuntungan District. Implementation is an action by individuals, officials, groups of government or private bodies directed at achieving the goals that have been outlined in a particular decision. This research uses implementation models according to Van Meter and Van Horn. The Implementation Model According to Van Meter and Van Horn includes, policy standards and objectives, resources, communication between implementing agencies, characteristics of implementing agencies, social, economic, and political environment, and attitude of implementers. This study uses a descriptive method with a qualitative approach. The research location is in Medan Tuntungan District. The sample in the study was 16 informants, where the determination of the informants used purposive sampling technique. Data collection techniques with interviews, field observations, and documentation. Data analysis using qualitative techniques. The results showed that the implementation of the rehabilitation program for uninhabitable houses (R-RTLH) in Medan Tuntungan District had been going well and was in accordance with the theory the model of implementation according to Van Meter and Van Horn.